Understanding torquetenovirus (TTV) as an immune marker - Edmund J. Gore; Lilli Gard; Hubert G. M. Niesters; Coretta C. Van Leer Buter (Frontiers in Medicine, 2023)
Torquetenovirus (TTV), a small, single stranded anellovirus, is currently being explored as a marker of immunocompetence in patients with immunological impairment and inflammatory disorders. TTV has an extremely high prevalence and is regarded as a part of the human virome, the replication of which is controlled by a functioning immune system. The viral load of TTV in plasma of individuals is thought to reflect the degree of immunosuppression. Measuring and quantifying this viral load is especially promising in organ transplantation, as many studies have shown a strong correlation between high TTV loads and increased risk of infection on one side, and low TTV loads and an increased risk of rejection on the other side. As clinical studies are underway, investigating if TTV viral load measurement is superior for gauging antirejection therapy compared to medication-levels, some aspects nevertheless have to be considered. In contrast with medication levels, TTV loads have to be interpreted bearing in mind that viruses have properties including transmission, tropism, genotypes and mutations. This narrative review describes the potential pitfalls of TTV measurement in the follow-up of solid organ transplant recipients and addresses the questions which remain to be answered.